Round and round : kids' songs for mixed ages [compact disc] - Block, Mike (Bright Shiny Things, 2022)
Since becoming a father 3 years ago, I've become intimately aware of so many classic songs for children. The appeal of these songs span many countries and centuries, and there is a simple genius to the best of them. This album was a cathartic experience, reclaiming songs I've heard a million times by engaging with them creatively and exploring their limits. My hope is that kids can enjoy listening to these familiar songs in a new way, while also providing some extra interest for the parents in the room, as well.